Peningkatan Literasi Keuangan UMKM melalui Pelatihan Pencatatan Hutang dan Piutang - Elysabet Christy Diandra Selano (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2026)
This community service activity aimed to improve the financial literacy of Micro, Small, and Medium Enterprises (MSMEs) through training on accounts receivable and payable recording using Microsoft Excel. The activity was motivated by the finding that MSME partners of Universitas Bina Nusantara (Binus) Malang still relied on unstructured manual recording, making it difficult to monitor cash flow and business financial positions. It was carried out in four stages, that are need assessment, material and recording-template design, training delivery, and evaluation. A participatory training approach was applied, combining conceptual material presentation with live demonstration and hands-on practice. The need assessment identified receivables and payables as the focus, as they are the most frequent yet most neglected transactions in participants' recording practices. Evaluation was conducted observationally, without pre-test or post-test. The results showed that all participants were able to follow the demonstration through to producing balance summaries and engaged actively in substantive discussions. The activity successfully built participants' awareness of systematic recording and provided initial digital recording skills. These outcomes are positioned as initial outputs that require further mentoring to become sustainable habits.